Effects of Aging on the Antioxidant Capacity of Red Wines - Lissi-Gervaso, E; Campos-Deramond, A; Campos-Deramond, A; Calderon-Espinoza, C; Calderon-Espinoza, C (Elsevier Inc., 2014)
Red wines possess large amounts of phenols and polyphenolic compounds that confer on them a high antioxidant capacity. This property, which has been associated with beneficial effects when ingested in moderate quantities, depends on a large number of factors. In particular, the variety of factors associated with wine aging makes it difficult to make even a semi-quantitative prediction of the effect of barrel and/or bottle aging on the antioxidant capacity of a given wine. It is remarkable that the acceptance of a red wine, and therefore its retail price, is practically unrelated to its antioxidant capacity and, hence, to its potential beneficial effects and is totally determined by its organoleptic properties. © 2014 Elsevier Inc. All rights reserved.